EFEKTIFITAS UU NO. 18 TAHUN 2012 TENTANG PANGAN DALAM MENGATASI PENGGUNAAN ZAT BERBAHAYA PADA PRODUK PANGAN DI INDONESIA GUNA MELINDUNGI KONSUMEN - Agustini, Sri (Ensiklopedia of Journal, 2024)
Consumer protection regarding safe and healthy food products is a significant challenge in Indonesia, especially concerning the use of harmful substances on vegetable crops. Local farmers often use pesticides and other chemicals in an uncontrolled manner, leaving dangerous residues on food products that eventually enter the market. The lack of supervision and information about food quality makes consumers vulnerable to health risks. This study aims to evaluate the effectiveness of Law No. 18 of 2012 concerning Food in addressing the issue of harmful substances in food products and protecting consumers. The research method used is descriptive-analytical, examining the implementation of Law No. 18 of 2012 in the supervision and regulation of harmful substances in food. The study identifies challenges and shortcomings in the implementation of the law, as well as its impact on food safety and consumer health. The findings indicate that although Law No. 18 of 2012 provides a comprehensive regulatory framework, there are various obstacles in its implementation, including inadequate supervision, lack of law enforcement, and minimal consumer education.Keywords: Food, Harmful Substances, Consumer Protection